Quantitative Easing and Credit Rating Agencies - Abidi, Nordine (IMF Working Papers; Working Paper, 2022)
This paper investigates the behaviour of credit rating agencies using a natural experiment in monetary policy. We exploit the corporate QE of the Eurosystem and its rating-based specific design which generates exogenous variation in the probability for a bond of becoming eligible for outright purchases. We show that after the launch of the policy, rating activity was concentrated precisely on the territory where the incentives of market participants are expected to be more sensitive to the policy design. Our findings contribute to better assessing the consequences of the explicit reliance on CRAs ratings by central banks when designing monetary policy. They also support the Covid-19 monetary stimulus, and in particular the waiver of private credit rating eligibility requirements applied to recently downgraded issuers.